Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To solve the given system of linear equations step-by-step, we have:
[tex]\[ \begin{cases} 2x + y = 4 \quad \text{(1)} \\ x + y = -2 \quad \text{(2)} \\ \end{cases} \][/tex]
Step 1: Subtract Equation (2) from Equation (1). This will eliminate [tex]\( y \)[/tex] and allow us to solve for [tex]\( x \)[/tex].
[tex]\[ (2x + y) - (x + y) = 4 - (-2) \][/tex]
Simplify the left-hand side:
[tex]\[ 2x + y - x - y = 4 + 2 \][/tex]
This reduces to:
[tex]\[ x = 6 \][/tex]
So, we have found that:
[tex]\[ x = 6 \][/tex]
Step 2: Substitute [tex]\( x = 6 \)[/tex] into Equation (2) to solve for [tex]\( y \)[/tex].
Recall Equation (2):
[tex]\[ x + y = -2 \][/tex]
Substitute [tex]\( x = 6 \)[/tex]:
[tex]\[ 6 + y = -2 \][/tex]
Solving for [tex]\( y \)[/tex]:
[tex]\[ y = -2 - 6 \][/tex]
[tex]\[ y = -8 \][/tex]
So, we have found that:
[tex]\[ y = -8 \][/tex]
Conclusion: The solution to the system of equations is:
[tex]\[ (x, y) = (6, -8) \][/tex]
So, the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that satisfy both equations are:
[tex]\[ x = 6 \quad \text{and} \quad y = -8 \][/tex]
[tex]\[ \begin{cases} 2x + y = 4 \quad \text{(1)} \\ x + y = -2 \quad \text{(2)} \\ \end{cases} \][/tex]
Step 1: Subtract Equation (2) from Equation (1). This will eliminate [tex]\( y \)[/tex] and allow us to solve for [tex]\( x \)[/tex].
[tex]\[ (2x + y) - (x + y) = 4 - (-2) \][/tex]
Simplify the left-hand side:
[tex]\[ 2x + y - x - y = 4 + 2 \][/tex]
This reduces to:
[tex]\[ x = 6 \][/tex]
So, we have found that:
[tex]\[ x = 6 \][/tex]
Step 2: Substitute [tex]\( x = 6 \)[/tex] into Equation (2) to solve for [tex]\( y \)[/tex].
Recall Equation (2):
[tex]\[ x + y = -2 \][/tex]
Substitute [tex]\( x = 6 \)[/tex]:
[tex]\[ 6 + y = -2 \][/tex]
Solving for [tex]\( y \)[/tex]:
[tex]\[ y = -2 - 6 \][/tex]
[tex]\[ y = -8 \][/tex]
So, we have found that:
[tex]\[ y = -8 \][/tex]
Conclusion: The solution to the system of equations is:
[tex]\[ (x, y) = (6, -8) \][/tex]
So, the values of [tex]\( x \)[/tex] and [tex]\( y \)[/tex] that satisfy both equations are:
[tex]\[ x = 6 \quad \text{and} \quad y = -8 \][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.